Determination of the location of air objects in polistatic radar system parasitising on radiation telecommunication systems - E. G. Borisov (Научный вестник МГТУ ГА, 2018)
Currently, in areas of large cities there is a steady trend towards an increase in the spatial density of telecommunications systems. Saturation of the radio spectrum with analogue and digital systems used to solve problems of radio communication and television allows on their basis improving the technologies for semi-active radar detecting and determining the coordinates of air objects. The introduction of radar surveillance using transmitters not intended for radar purpose is often called a semi-active radar using outside or “parasitic” emission sources. The advantages of the systems are the minimization of the deployment costs, low operational energy costs, a low probability of establishing distortions, stealth operation, environmental friendliness and lack of requirements for radio frequency resource allocation.  The relatively large elevations of the antennas of communication and television transmitters with the existing emitted power create favorable conditions for the detection of low altitude air objects. The digital signals of modern telecommunications systems have a spectrum width that provides acceptable resolution and accuracy for measuring the full range and angular coordinates. In general, a system of this type is a poly-static (multi-static) system consisting of one or more radiation sources and one or more receiving positions scattered in space. The promising task such systems solve along with airspace control is air traffic control. The article considers options for determining the rectangular coordinates of air objects in a system of bistatic radar stations using radio emission from external sources for target detection. The variants of the location of air objects with different composition of primary measurements of coordinates and a number of transmitting positions are considered. Analytical expressions are given for calculating the projections of the target velocity vector on the axis of the Cartesian coordinate system. The accuracy of airborne positioning for multi-static radar systems of this type is estimated.